CAR T- cell therapy provides an opportunity for further consolidation treatment for relapsed or refractory adult Burkitt lymphoma patients - Liu, Rui; Yang, Fan; Ma, Lixia; Guo, Yuelu; Cao, Miaomiao; Fu, Zhonghua; Deng, Biping; Zheng, Qinlong; Chen, Chen; Li, Danyang; Ke, Xiaoyan; Hu, Kai (Frontiers in Oncology, 2025)
BackgroundRelapsed or refractory (R/R) Burkitt lymphoma (BL) in adults is aggressive and lacks standardized salvage options. Data on the efficacy and safety of chimeric antigen receptor T (CAR-T) cell therapy in this population remains limited.MethodsWe retrospectively analyzed 25 adult patients with relapsed or refractory Burkitt lymphoma who received CAR T-cell therapy. Clinical data, treatment responses, and survival outcomes were collected from medical records. Bridging therapy and lymphodepleting regimens varied based on disease status. Treatment-related toxicities and CAR-T expansion were monitored. Primary endpoints included efficacy, safety, and survival. Risk factors associated with treatment outcomes were explored using univariate analyses.ResultsOne month objective response rate (ORR) was 52%(13/25)(95%CI: 31.3–72.2), with a complete response rate (CRR) of 28% (7/25). Sixteen patients (64%) received sequential consolidation therapy including 9 who received a second CAR-T infusion, and 7 who proceeded to autologous or allogeneic hematopoietic stem cell transplantation. The median follow-up time was 26.10 months (range 14.50-57.17). The median OS was 5.49 months(95%CI 1.74-9.25), and the median PFS was 2.96(95%CI 1.62-4.3)months. At last follow-up(2024-08-22), 28% achieved disease-free survival, with one patient disease-free for 5 years.ConclusionsCAR-T therapy shows promising activity in relapsed/refractory Burkitt lymphoma, but its effectiveness is limited by short response duration. High-risk features may predict poor outcomes, and a higher number of long-term survivors were observed in patients who received transplant sequential consolidation. However, due to the small sample size, larger studies are needed to validate these findings.